Biochemical and genetic characterization of bacteria isolated from diseased rainbow trout (Oncorhynchus mykiss) farmed in Lesotho and Mpumalanga province of South Africa - Kutu, Vuyokazi (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.